Are iron-phosphate minerals a sink for phosphorus in anoxic Black Sea sediments? - Nikki Dijkstra; Peter Kraal; Marcel M M Kuypers; Bernhard Schnetger; Caroline P Slomp (PLoS ONE, 2014)
Phosphorus (P) is a key nutrient for marine organisms. The only long-term removal pathway for P in the marine realm is burial in sediments. Iron (Fe) bound P accounts for a significant proportion of this burial at the global scale. In sediments underlying anoxic bottom waters, burial of Fe-bound P is generally assumed to be negligible because of reductive dissolution of Fe(III) (oxyhydr)oxides and release of the associated P. However, recent work suggests that Fe-bound P is an important burial phase in euxinic (i.e. anoxic and sulfidic) basin sediments in the Baltic Sea. In this study, we investigate the role of Fe-bound P as a potential sink for P in Black Sea sediments overlain by oxic and euxinic bottom waters. Sequential P extractions performed on sediments from six multicores along two shelf-to-basin transects provide evidence for the burial of Fe-bound P at all sites, including those in the euxinic deep basin. In the latter sediments, Fe-bound P accounts for more than 20% of the total sedimentary P pool. We suggest that this P is present in the form of reduced Fe-P minerals. We hypothesize that these minerals may be formed as inclusions in sulfur-disproportionating Deltaproteobacteria. Further research is required to elucidate the exact mineral form and formation mechanism of this P burial phase, as well as its role as a sink for P in sulfide-rich marine sediments.